Modification of Urushiol Derivatives by Liquid Crystal Epoxy Resin - Gongwen Tang; Zhishan Yan; Linrong Ma; Xin Huang (International Journal of Polymer Science)
Urushiol derivatives have vast potentials for using as coating materials. However, the cured coatings are quite brittle, limiting their applications. In this study, urushiol-furfural (UFUR) was chosen as an example of urushiol derivatives and a liquid crystal (LC) epoxy resin, tetramethylbiphenyl diglycidyl ether (TMBPDE), was for the first time utilized to modify UFUR. Fourier transform infrared spectroscopy and solid-state 13C nuclear magnetic resonance showed the reactions between TMBPDE and UFUR after the UFUR/TMBPDE composite resin was cured. Differential scanning calorimetry analysis showed that the Tg significantly increased after the addition of TMBPDE. Thermogravimetry analysis indicated that the cured UFUR/TMBPDE composite resin exhibited increasing thermodecomposition temperature as the TMBPDE concentration increased, indicating its great potential for high temperature applications. Moreover, the presence of TMBPDE enhanced the toughness of UFUR as observed by impact test and reflected in the morphologies observed from SEM images of fracture surfaces. It would also be novel and effective to modify urushiol derivatives by the LC polymer.